Professional identity of a French language teacher in Poland: constancy vs. change, sameness vs. difference, agency - Werbińska, Dorota (Glottodidactica, 2022)
Studies conducted on teacher identity have mostly focused on preservice language teachers. By contrast, this study looks at the professional identity of a veteran teacher of French as a foreign language in Poland. It describes a two-stage biographic study in which the narratives obtained are subjected to semantic deconstruction with the application of Bamberg’s (2010) model of identity. To this end, the author investigates: 1) what is constant and what changes in the participant’s professional career in terms of the emotions she experiences, 2) what are the similarities and differences between the teachers she refers to and herself, 3) what is the role of agency in the participant’s professional decisions. Through the analysis, the Author seeks to find out with what content Bamberg’s identity pillars may be filled, what teacher emotions and feelings can be inferred from what is said, and what insights can be gained into the identity of a French language teacher in Poland.